Use of Trastuzumab for Breast Cancer: The Role of Age - Mazzucco, Walter; Rossi, Marta; Cusimano, Rosanna; Franchi, Matteo; Bonifazi, Martina; Mistretta, Alessandro; Vitale, Francesco; Ricciardi, Walter; Negri, Eva; Boccia, Stefania; La Vecchia, Carlo (Current Pharmaceutical Design, 2014)
Indication for the use of trastuzumab was given in Italy in 2000 for the treatment of HER-2 metastatic breast cancer and in 2006 for early stage breast cancer. Information on trastuzumab use and on its possible variation with age in Italy is however limited. Using health care administrative databases, we evaluated the prevalence of the use of trastuzumab, and the probability for administration since the first hospitalization for breast cancer in various age groups, in two series of Italian women diagnosed with breast cancer in the Lombardy region (2004-2009) and in the Palermo district. The ratio between trastuzumb users and patients with a hospitalization for breast cancer increased from 2.9% in 2004 up to 17.2% in 2009 in Lombardy. Patients aged <65 years were more frequent users (9.6%) compared to those aged ≥ 75 years (1.3%). Similarly, in the Palermo district the ratio increased from 10.6% in 2006 to 28.5% in 2008, with subjects aged <65 years more frequently using trastuzumab (19.1%), than subjects aged ≥ 75 years (6.2%). The age ratio between younger and older patients decreased over time in both settings (from 15 in 2004 to 10.2 in 2006, and 5.2 in 2009 in Lombardy, and from 4.0 in 2006 to 2.3 in 2009 in the Palermo district). The proportion of breast cancer patients using trastuzumab increased over time both in Lombardy and in Palermo district, though geographical differences persisted. Younger breast cancers patients were more likely to receive a trastuzumab treatment than elderly ones, but the difference declined over calendar period.
Keywords: metastatic breast cancer